ANALISIS PENGARUH LDR, NPL, NIM, INFLASI, DAN UKURAN BANK TERHADAP KINERJA KEUANGAN BANK (Studi pada Bank Pembangunan Daerah Konvensional di Indonesia Periode 2015- 2019) - Putra, Deni Riwandha; Sampurno, Raden Djoko (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This study aims to analyze the effect of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Net Interest Margin (NIM), inflation, and bank size on bank financial performance as measured by Return On Asset (ROA). The population used in this study is the conventional Regional Development Banks in Indonesia for the 2015-2019 period. The sampling technique used purposive sampling method. The number of samples obtained is 23 banks. Data were obtained from the annual reports of each bank and from the Central Statistics Agency. Data were analyzed using multiple linear regression analysis model which includes classical assumption test, F statistic test, t statistic test. The results of this study indicate that LDR has no significant and positive effect on bank financial performance, NPL has significant and negative effect on bank financial performance, NIM has significant and positive effect on bank financial performance, Inflation has no significant and positive effect on bank financial performance, bank size has no significant and negative effect on bank financial performance. Simultaneous test results show that the variables of LDR, NPL, NIM, inflation, and bank size simultaneously affect the bank financial performance.